Cosolvent action of promethazine hydrochloride in (ethyl acetate + alcohols) and thermodynamic property analysis. (April 2020) - Yang, Zehui; Shao, Danfeng; Zhou, Guoquan
Graphical abstract: Highlights: Research the solubility profiles of promethazine hydrochloride in pure and mixed solvents. Discuss the effect of solvent properties on the dissolution process. The interaction between promethazine hydrochloride molecule and solvent molecules was analyzed. Some thermodynamic properties of dissolution process are evaluated. Abstract: This study presents the solubility profiles of promethazine hydrochloride in pure and mixed solvents. The effects of temperature and composition of mixed solvents on solubility were investigated. Maximum solubility value was obtained in n -propanol in pure solvents, and in ethyl acetate, it is the lowest. While in two mixtures of ethyl acetate (1 −  w ) + ethanol ( w, mass fraction ) and ethyl acetate (1 −  w ) +  iso propanol ( w ), the values increased monotonically with the increasing temperature, and increased with increasing co-solvent (alcohols) mass fraction ( w ) to a maximum value at w  = 0.4 and then decreased. The interaction between promethazine hydrochloride molecule and solvent molecules was discussed. The function of temperature and solvent composition in pure and binary mixed solvents was evaluated by some thermodynamic models. The dissolution thermodynamic properties, including enthalpy, entropy and Gibbs energy of promethazine hydrochloride in the dissolution process were evaluated using the van't Hoff equation. The results indicate that in all selected solvents the dissolution behavior were endothermic and entropy-driven.